The Density Functional Tight Binding (DFTB) Approach for Investigating Vacancy and Doping in Graphene as Hydrogen Storage - Hidayat, Yuniawan; Rahmawati, Fitria; Dwi Nugrahaningtyas, Khoirina; Bagus Swandito, Paulus (Universitas Andalas, 2024)
A study on graphene defects for hydrogen storage has been successfully conducted using the Density Functional Tight Binding (DFTB) approach. The research aimed to modify solid materials for hydrogen storage. A 4 × 4 × 1 unit cell was used as the basis, while the supercell used for sampling was enlarged to 40 × 40 × 1. The analyzed data included changes in Density of States (DOS), Fermi level shifts, electronic band structures, formation energy, adsorption energy, and isosurfaces for each graphene orientation. It has been observed that modifying the surface structure of graphene can alter the electronic properties of graphene. This is indicated by shifts in DOS intensity, characterized by increased electronic intensity around the Fermi level total density charge different. The interaction energy between graphene and hydrogen gas has been determined to be -0.0155 eV for H-epoxy graphene, -0.4941 eV for H-monovacancy graphene, and -0.0424 eV for HN-monovacancy graphene. The presence of the vacancy increase the potential to adsorp hydrogen.